2024
DOI: 10.1111/cas.16082
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole inhibits tumor growth via CEBPB‐mediated glycolysis in colorectal cancer

Yong Zhang,
Lu Li,
Feifei Chu
et al.

Abstract: Advanced colorectal cancer (CRC) is characterized by a high recurrence and metastasis rate, which is the primary cause of patient mortality. Unfortunately, effective anti‐cancer drugs for CRC are still lacking in clinical practice. We screened FDA‐approved drugs by utilizing targeted organoid sequencing data and found that the antifungal drug itraconazole had a potential therapeutic effect on CRC tumors. However, the effect and mechanism of itraconazole on CRC tumors have not been investigated. A cell line‐der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Several studies indicate that CEBPB and CEBPD promote metabolic reprogramming and affect glycolysis in various cancer cell types [ 20 , 21 , 22 , 23 , 24 , 25 ]. Recently, Zhang et al [ 25 ] showed evidence that CEBPB promotes glycolysis in colon cancer cells by elevating ENO1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies indicate that CEBPB and CEBPD promote metabolic reprogramming and affect glycolysis in various cancer cell types [ 20 , 21 , 22 , 23 , 24 , 25 ]. Recently, Zhang et al [ 25 ] showed evidence that CEBPB promotes glycolysis in colon cancer cells by elevating ENO1.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that CEBPB and CEBPD promote metabolic reprogramming and affect glycolysis in various cancer cell types [ 20 , 21 , 22 , 23 , 24 , 25 ]. Recently, Zhang et al [ 25 ] showed evidence that CEBPB promotes glycolysis in colon cancer cells by elevating ENO1. They reported that CEBPB knockdown diminished ENO1 expression and caused a small but significant decrease in glycolysis in HCT116 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation